2021
DOI: 10.52088/ijesty.v1i2.120
|View full text |Cite
|
Sign up to set email alerts
|

Space Pattern of Samudera Pasai Sultanate

Abstract: Samudera Pasai is one of the Islamic Sultanates in Indonesia which appeared in the Middle Ages or around 1267 AD. Evidence of the existence of the Sultanate of Samuedra Pasai in Indonesia is listed in the book Rihlah ilal-Masyriq (Wanderings to the East) written by Abu Abdullah Ibnu Batutha (1304 - 1368 AD), a Muslim adventurer who traveled to Samudera Pasai in 1345 AD. The spatial pattern of the Samudera Pasai Sultanate is no longer visible because there are no traces of archaeological remains in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…So HEART is part of the reliability calculation, which is defined as how much the operator makes an error in the task that should be done [15], [16]. The steps taken to determine the value of Human Error Probability (HEP) using the HEART method are as follows [17]:…”
Section: Human Error Assessment and Reduction Technique (Heart)mentioning
confidence: 99%
“…So HEART is part of the reliability calculation, which is defined as how much the operator makes an error in the task that should be done [15], [16]. The steps taken to determine the value of Human Error Probability (HEP) using the HEART method are as follows [17]:…”
Section: Human Error Assessment and Reduction Technique (Heart)mentioning
confidence: 99%
“…This city becomes a vital economic and trading distribution linkage between Medan, the capital city of North Sumatera Province, and Banda Aceh, the capital city of Aceh Province. One of the most active trading centers in Lhokseumawe is the Inpres Market; this traditional market is located downtown and has various commercial activities, public services, and settlements [7]. The Inpres consists of 2 (two) market areas: Pujasera Market and Old Market.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of city dwellers in green open spaces that are harmonious, healthy, and sustainable have shown that green open space is not only an environment that can balance the quality of the city environment, but also greatly affects the mental health of residents in the scope of social activities in it. Therefore, research is needed on the attractiveness of the local community as a symbol of identity [6] comes from the pattern of social activities of the residents of Binjai City as a domain of identification of the green open space in the city of Binjai for a certain principle or reference approach as an instrument for recommending the provision of green open space as a space to balance the face of the city that has no direction for the cause of its existence [7].…”
Section: Introductionmentioning
confidence: 99%